Dietary Inclusion of Feed Additives in Broilers: Effect on Carcass Characteristics, Visceral and Lymphoid Organs and Gut Health - Solanki, Mayur; Verma, Kuldeep Kumar; Singh, Rana Ranjeet; Rao, Thakur Krishna Shankar (Indian Journal of Animal Nutrition, 2021)
The present experiment was conducted on 288-day-old unsexed broiler chicks to evaluate the effect of dietary feed additives viz. neem leaf meal (NLM) and citric acid (CA) on carcass characteristics, visceral and lymphoid organs, and gut health in broiler chickens. The chicks were randomly distributed into 6 dietary groups of 48 birds per group, each having 4 replicates (12 birds per replicate) in a randomized block design. The birds were fed on a standard diet without any supplementation control (T0); and with supplementation of NLM 2.5 g/kg of feed (T1); CA 15 g/kg of feed (T2); CA 25 g/kg of feed (T3); NLM 2.5 g + CA 15 g/kg of feed (T4); NLM 2.5 g + CA 25 g/kg of feed (T5). Eight birds from each treatment (2 per replicate) were randomly selected for slaughter and collection of samples and microbial study at day 42. The yield of the carcass, cut-up parts, and visceral organs, and length of the small intestine revealed comparable values without any adverse effect in the groups. The caecal E. coli population reduced significantly (P